Indirect responsibility for terrorist acts: redefinition of the concept of terrorism beyond violent acts - Lehto, Marja (Monographs on international law and human rights)
The international law of terrorism -- Terrorist crimes within the framework of international criminal law -- Extended responsibility in international criminal law : jurisprudence -- Extended responsibility in international criminal law : codifications and an emerging doctrine -- State responsibility for international crimes -- The criminalisation of terrorist financing -- The follow-up to the terrorist financing convention -- Beyond criminal law : the role of the UN Security Council in enhancing accountability for terrorist acts -- Implications on state responsibility for terrorist acts